Digital Narratives: Representations of Bali in Virtual Tourist Communities - Bestari, Ni Made Prasiwi; Shantika, Budi; Wulandari, Pande Putu (Humanis; Vol 28 No 4 (2024)DO - 10.24843/JH.2024.v28.i04.p04, 2024)
The digital narratives within virtual tourist communities on Bali highlight the island’s rich cultural heritage through diverse themes and discussions. Platforms like TripAdvisor, Facebook, and Reddit play a significant role in shaping perceptions, providing a space where travelers share experiences and insights. Key themes include romanticized portrayals, spirituality, cultural exchange, and ethical considerations, collectively shaping a nuanced digital portrayal of Bali. This analysis was carried out using qualitative methods to explore these narratives and uncover underlying motivations, sentiments, and cultural insights shared within the communities. Ultimately, these discussions encourage responsible tourism and promote Bali’s unique cultural values on a global scale. The significance of this research lies in demonstrating how digital spaces can foster meaningful connections between global audiences and local cultures. By promoting environmental and cultural awareness, these virtual communities help preserve Bali’s identity and heritage in the face of increasing mass tourism.